A Case Report of Metastatic Castration-Resistant Prostate Cancer Harboring a PTEN Loss - Myint, Zin W.; Allison, Derek B.; Ellis, Carleton S. (Frontiers in Oncology, 2021)
The treatment landscape of metastatic castration resistant prostate cancer (mCRPC) has dramatically improved over the last decade; however, patients with visceral metastases are still faced with poor outcomes. Phosphatase and tensin homolog (PTEN) loss is observed in 40-60% of mCRPC patients and is also associated with a poor prognosis. Several PI3K/AKT/mTOR pathway inhibitors have been studied with disappointing anti-tumor activity. Here we present a case of a patient with heavily treated mCRPC who had a modest tumor response to concurrent carboplatin, abiraterone acetate/prednisone, and liver-directed radiation therapy. We discuss the potential rationale supporting the use of this combination therapy and its safety in mCRPC. While the underlying basic mechanism of our patient’s anti-tumor response remains uncertain, we suggest that further prospective studies are warranted to evaluate whether this combination therapy is effective in this population of patients with pre-treated mCRPC and PTEN loss.